Pediatric Masked Mastoiditis Associated with Multiple Intracranial Complications. (28th June 2015) - Voudouris, Charalampos; Psarommatis, Ioannis; Nikas, Ioannis; Kafouris, Dimitrios; Chrysouli, Konstantina
Abstract : Masked mastoiditis is a distinct form of mastoiditis with little or no symptomatology, characterized by its potential to generate severe otogenic complications. Therefore, suspected masked mastoiditis should be diagnosed and treated without delay. This study reports a rare case of masked mastoiditis, manifested by multiple intracranial complications in an immunocompetent girl. The child exhibited headache and neurological symptomatology. Imaging studies revealed an epidural and a large cerebellar abscess and the patient was immediately treated with a triple antibiotic therapy. Mastoid surgery and drainage of the epidural abscess took place after the stabilization of the patient's neurologic status, on the 3rd hospitalization day. The cerebellar abscess was treated by craniectomy and ultrasound-guided needle aspiration in the 3rd week of hospitalization. The girl was finally discharged in excellent condition. Two years later, she is still in good health, without otological or neurological sequelae. Masked mastoiditis is an insidious disease which requires increased clinical awareness and adequate imaging. Should clinical and/or radiological findings be positive, mastoidectomy must follow in order to prevent severe otogenic complications that can be triggered by masked mastoiditis.